Numerical Thermo-Structural Simulations for the Design of the Havar Beam Window of a Beryllium Target for Neutron Beam Production - Roberta Dattilo (Engineering Proceedings, 2025)
The present work was carried out as part of the PRIN 2022JCS2CN project “CoolGal”, which aims to design and manufacture a beryllium target cooled by Galinstan (a liquid metal alloy at room temperature) for the production of neutrons using energetic protons. The objective of the present work is to thermo-structurally design a beam window that encloses the environment in which the target is housed. The window consists of a Havar disk, the thickness of which must be minimized to absorb the least amount of proton beam power, while its diameter must be sufficient to avoid excessive beam loss. The window will then be embedded around its perimeter and will have to withstand two load conditions, applied individually: A mechanical load, due to the atmospheric pressure of 0.11 MPa during vacuuming, and a thermal load, due to heating during irradiation with the proton beam. Once a first-version window geometry was defined, a static structural finite element analysis (FEA) was carried out by activating geometric nonlinearities to assess the structural integrity of the window under mechanical loading. After that, a static thermal–mechanical FEA analysis was carried out to assess the structural integrity of the window under thermal loading. Given the compressive stress state induced by thermal loading and the slenderness of the window itself, a nonlinear buckling structural FEA analysis was also performed.